2005
DOI: 10.1113/jphysiol.2005.086280
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial redox state and Ca2+ sparks in permeabilized mammalian skeletal muscle

Abstract: Intact skeletal muscle fibres from adult mammals exhibit neither spontaneous nor stimulated Ca 2+ sparks. Mechanical or chemical skinning procedures have been reported to unmask sparks. The present study investigates the mechanisms that determine the development of Ca 2+ spark activity in permeabilized fibres dissected from muscles with different metabolic capacity. Spontaneous Ca 2+ sparks were detected with fluo-3 and single photon confocal microscopy; mitochondrial redox potential was evaluated from mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 56 publications
2
75
0
2
Order By: Relevance
“…Another elegant study identified a subset of mitochondria that displayed a rise in [Ca 2+ ] m upon caffeine stimulation even when global [Ca 2+ ] c transients were buffered by BAPTA, further supporting a local SR-mitochondrial Ca 2+ transfer (Shkryl and Shirokova, 2006). Furthermore, mitochondria were found to attenuate spontaneous [Ca 2+ ] c sparks and transients in proportion to their abundance in fibers (Isaeva et al, 2005).…”
Section: Mitochondria Camentioning
confidence: 99%
See 1 more Smart Citation
“…Another elegant study identified a subset of mitochondria that displayed a rise in [Ca 2+ ] m upon caffeine stimulation even when global [Ca 2+ ] c transients were buffered by BAPTA, further supporting a local SR-mitochondrial Ca 2+ transfer (Shkryl and Shirokova, 2006). Furthermore, mitochondria were found to attenuate spontaneous [Ca 2+ ] c sparks and transients in proportion to their abundance in fibers (Isaeva et al, 2005).…”
Section: Mitochondria Camentioning
confidence: 99%
“…Mitochondria occupy ,40% of the cell volume in cardiomyocytes and ,20% in skeletal muscle fibers (Isaeva et al, 2005) and are mostly located among the myofibrils. In ventricular cardiomyocytes, intermyofibrillar mitochondria fill the space parallel with the myofibrils, whereas in skeletal muscle fibers, mitochondria are localized close to the CRUs (see Fig.…”
Section: Box 1 Structural Organization Of the Musclementioning
confidence: 99%
“…23 It was found that prolonged IGF-I treatment in mdx mice can induce muscle fibers from a fast-twitch phenotype toward the slow-twitch phenotype without a change in fiber cross areas. 22 Compared with fasttwitch muscle, slow-twitch muscle fibers are rich in mitochondria, 24 have higher oxidative capacities, 25 and therefore use ATP in a more efficient way and produce less ROS, which would cause less or no damage to muscle cells. Our finding that IGF-I is able to prevent muscle cell from H 2 O 2 -induced cell death and recover cell viability may offer a rational explanation for IGF-I conferring protection on dystrophic muscle from contraction-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mitochondria-derived ROS, generated from diazoxide (an ATP-sensitive K + channel opener)-induced mitochondrial depolarization, elevates Ca 2+ spark frequency and enhances the coupling of sparks to Ca 2+ -sensitve K + channels in smooth muscle cells [63] . In permeabilized rat skeletal muscle fibers, 50 µmol/L H 2 O 2 was also found to increase Ca 2+ spark frequency [64] . More direct evidence is needed to confirm the regulation of local and global Ca 2+ signals by mitochondria-derived ROS in physiological and pathological conditions.…”
Section: Local Camentioning
confidence: 99%